2005
DOI: 10.1111/j.1742-1241.2005.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac syndrome X

Abstract: Cardiac syndrome X, the triad of angina pectoris, a positive exercise electrocardiogram for myocardial ischaemia and angiographically smooth coronary arteries, is frequently associated with debilitating symptomology, increased psychological morbidity and a poor quality of life. While various avenues of research have been undertaken, there are as yet no definitive conclusions regarding the exact pathogenesis of the condition. A number of physiological mechanisms have been explored, including the existence of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 67 publications
0
32
0
Order By: Relevance
“…Intramyocardial microvascular changes, such as hyaline deposits in arterioles and capillary basement membrane thickening [70], have been reported in association with diabetes mellitus, although not consistently [71,72] and without a clear association with cardiac dysfunction [70]. Clinically, small vessel disease may be manifest as angina type symptoms in the absence of macroscopic coronary artery disease, termed 'Syndrome X' [69, [73][74][75][76].…”
Section: Introductionmentioning
confidence: 98%
“…Intramyocardial microvascular changes, such as hyaline deposits in arterioles and capillary basement membrane thickening [70], have been reported in association with diabetes mellitus, although not consistently [71,72] and without a clear association with cardiac dysfunction [70]. Clinically, small vessel disease may be manifest as angina type symptoms in the absence of macroscopic coronary artery disease, termed 'Syndrome X' [69, [73][74][75][76].…”
Section: Introductionmentioning
confidence: 98%
“…Patients with coronary artery spasm (Prinzmetal's or variant angina), left ventricular (LV) hypertrophy, systemic hypertension, and valvular heart disease were not included to the definition of this syndrome [3,4]. Currently, cardiac syndrome X is defined by a typical angina pectoris with normal or near normal ( < 40% stenosis) coronary angiogram with or without any electrocardiographic (ECG) change or atypical angina pectoris with normal or near normal coronary angiogram plus a positive noninvasive test (exercise tolerance test or myocardial perfusion scan) with or without ECG changes [5][6][7][8][9]. Although some authors have claimed the presence of ischaemia was related with microvascular dysfunction in these patients, the pathophysiology of cardiac syndrome X has not been clearly established [7,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well recognized that chest pain with normal coronary arteries are termed as cardiac syndrome X. The patients with this syndrome often complain of debilitating and excruciating chest pain despite the presence of normal coronary arteries on angiography [15]. Although cardiac syndrome X is not associated with an increased risk of death, it often severely impairs quality of life and represents a substantial cost burden to the health care system [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, the investigation of RWD in cardiac syndrome X, a condition associated with endothelial activation and coronary microvascular dysfunction, has not been performed up to date. Moreover, emerging data suggested that inflammation might play a role in microvascular dysfunction in patients with cardiac syndrome X, and C-reactive protein (CRP) might a promising marker for this disorder [15][16][17].…”
Section: Introductionmentioning
confidence: 99%